Global Rice Market and Export Restriction - Mamun, Abdullah; Glauber, Joseph W. (2023)
Abdullah Mamun and Joseph Glauber IFPRI-AMIS SEMINAR SERIES A Look at Global Rice Markets: Export Restrictions, El Niño, and Price Controls Co-organized by IFPRI and Agricultural Market Information System (AMIS) OCT 18, 2023 - 9:00 TO 10:30AM EDT